Platelet to cholesterol ratio of high density lipoprotein cholesterol is associated with diabetes and comorbidity risk - Ani Umar; Firdayanti; Heni Umar; Angriani Fusvita; Susanti; Sri Aprilianti Idris (Gema Lingkungan Kesehatan, 2026)
This study aims to analyze the relationship between platelet to HDL cholesterol (Platelet to HDL Ratio / PHR) ratio and the presence of type 2 diabetes mellitus, as well as evaluate the ability of PHR as a predictor of comorbidity risk. Multivariate logistic regression analysis was used to estimate the odds ratio (OR) and 95% CI. The discriminatory ability of the model is evaluated with the receiver operating characteristic curve (ROC), with the area under the curve (AUC) used to measure the model's performance. Sensitivity and specificity. This study used a cross-sectional observational design with 220 participants (110 type 2 diabetes patients and 110 non-diabetic controls) from the Southeast Sulawesi Provincial General Hospital. Samples were selected based on inclusion criteria (age 30–70 years, for the diabetes group) and exclusion (such as anemia or use of anticoagulant drugs). Data were collected through clinical examinations (age, BMI, blood pressure, platelet count, HDL). PHR is calculated as the number of platelets (per μL) divided by HDL levels (mg/dL). Statistical analysis was performed using independent t-test, multivariate logistic regression, and ROC curve with SPSS software (p < 0.05). The results showed that PHR was significantly higher in the diabetes group with comorbidities (mean 5.49±2.10) than in healthy individuals (4.25±2.39; p < 0.001). The ROC curve shows an AUC of 0.70 for PHR in predicting comorbidity risk, better than HDL alone (AUC 0.55). This study shows that platelet-to-HDL ratio (PHR) is proven to be a simple and economical potential biomarker for detecting an association with diabetes and predicting the risk of vascular comorbidities. These findings support the use of PHR in routine clinical practice, especially in developing countries such as Indonesia. This research contributes to the strategy for the early prevention of diabetes complications through easily accessible hematological parameters.